(untitled) - Bouvier, Nicolas (Paris, France, 1991)
A grab bag of little trinkets, diamond bracelets, popcorn and flashy toys constitutes this collection of sketches about things, people and places Japanese, with dollops of history and mythology. Bouvier, an itinerant French journalist and photographer, roamed around the country on and off for some six years between the '50s and the '70s, sometimes going hungry and sleeping wherever he could find room for his portable mat, on occasion living elegantly with wife and son in a "Pavilion of the Auspicious Cloud" on the grounds of a monastery. Fluent, curious, entranced, Bouvier touches on nearly every aspect of Japanese culture and history. How to listen to the music, what Zen really is, what one Ainu said to another, why peasants rarely want to visit Tokyo, what the emperor of Japan said to the emperor of China, the graffiti on the walls, modern geishas, creation myths: such tidbits present a picture of the country rarely found in more scholarly studies or in guidebooks. The random organization can be irritating, but the information and insights are wonderful.